DIGITAL TRANSFORMATION IN MARITIME TRAINING FACILITIES: IOT-BASED WATER QUALITY MONITORING FOR ENHANCED SAFETY AND SUSTAINABILITY IN SEAFARER EDUCATION - Saifudin, Iksan; Palapa, Arika; Kalmareuro, Venda Uno; Sutopo, Fajar (Faculty of Administrative Science, Universitas Brawijaya, 2026)
This research investigated IoT-based water quality monitoring implementation in maritime education facilities, addressing safety assurance and digital transformation imperatives. A prototype system integrating ESP32 microcontroller with temperature, pH, TDS, and turbidity sensors was deployed at Politeknik Pelayaran Sulawesi Utara's training pool. Systematic validation against conventional instruments demonstrated exceptional accuracy for temperature (99.4%) and pH (99.46%) monitoring, with acceptable performance for TDS (97.39%) and turbidity (93.59%). Qualitative assessment through semi-structured interviews with maritime experts (n=8), lecturers (n=12), and graduates (n=15) revealed convergent recognition of enhanced safety assurance, operational efficiency gains, and digital competency development opportunities. Thematic analysis identified sustainability integration and pedagogical applications as secondary benefits supporting green campus initiatives and technology-enhanced learning. The research establishes empirical foundation for scaling IoT monitoring across maritime training institutions, particularly in resource-constrained contexts, demonstrating affordable sensor technologies can achieve measurement quality adequate for safety-critical applications while simultaneously creating authentic learning environments for developing maritime workforce digital competencies aligned with industry digitalization trends.